Out of Arabia-the settlement of island Soqotra as revealed by mitochondrial and Y chromosome genetic diversity - Cerný, Viktor; Pereira, Luísa; Kujanová, Martina; Vasíková, Alzbeta; Hájek, Martin; Morris, Miranda; Mulligan, Connie J (American journal of physical anthropology, 2009)
The Soqotra archipelago is one of the most isolated landmasses in the world, situated at the mouth of the Gulf of Aden between the Horn of Africa and southern Arabia. The main island of Soqotra lies not far from the proposed southern migration route of anatomically modern humans out of Africa approximately 60,000 years ago (kya), suggesting the island may harbor traces of that first dispersal. Nothing is known about the timing and origin of the first Soqotri settlers. The oldest historical visitors to the island in the 15th century reported only the presence of an ancient population. We collected samples throughout the island and analyzed mitochondrial DNA and Y-chromosomal variation. We found little African influence among the indigenous people of the island. Although the island population likely experienced founder effects, links to the Arabian Peninsula or southwestern Asia can still be found. In comparison with datasets from neighboring regions, the Soqotri population shows evidence of long-term isolation and autochthonous evolution of several mitochondrial haplogroups. Specifically, we identified two high-frequency founder lineages that have not been detected in any other populations and classified them as a new R0a1a1 subclade. Recent expansion of the novel lineages is consistent with a Holocene settlement of the island approximately 6 kya.
Keywords: Founder Effect; Social Isolation; Arabia; Geography; Chromosomes, Human, Y; lidský chromozom Y; DNA, Mitochondrial; Afrika; lidé; Anthropology, Physical; sociální izolace; zeměpis; Genetic Variation; Phylogeny; Arábie; Racial Groups; efekt zakladatele; Africa; Haplotypes; mitochondriální DNA; antropologie fyzická; rasové skupiny; haplotypy; fylogeneze; genetická variace; Humans